Porter's competitive strategies in fashion industry: case study - Marques, António Manuel Dinis Ribeiro (2017)
The Portuguese footwear industry had an excellent economic performance in the last six years. Innovation, own brands, entry in new markets and new products development are common approaches to the most competitive companies, some of them leaders in the European sector. This industry is traditional, mature and “low-tech”, with two main clusters in Portugal (both clusters are located in the north of Portugal). The paper will analyse the competitive strategies follow by seven footwear companies and will show the areas and components that the companies focus theirs resources and strategies to be more competitive and sustainable. The research methodology was qualitative and the strategy for obtaining data was the case study, with interviews, questionnaires and document analysis. The economic results of the footwear companies studied highlight the differences between all of them and these differences are related with the competitive strategy adopted. Cooperation is very strong in many common projects, coordinated by the sectorial organizations (APICCAPS and CTCP). Private label regime remains dominant in the sector but year by year companies are going to new directions: own products, own brands and entry in new markets. Future researches should enhance the strategic options of companies in these important and traditional sectors of the Portuguese economy.